Complementary medicine use in multi-ethnic paediatric outpatients - Robinson,N; Blair,M; Lorenc,A; Gully,N; Fox,P; Mitchell,K (Complementary Therapies in Clinical Practice, 2008)
Objective: To determine the prevalence and determinants of complementary medicine (CM) use in a multi-ethnic paediatric outpatient population. Methodology: A parent-completed questionnaire survey of paediatric outpatients attending general and sub-specialist outpatient clinics at a North West London hospital during September to December 2005. Results: Parents’ use of CM for their children in this multi-ethnic population was higher than expected at 37%. Use was correlated with parental CM use and education but independent of ethnic group. Parental CM use and child’s health status were significant predictors of child CM use. The main reason for using CM was word of mouth (45%) and the main source of information was friends and family (51%). The most popular treatments used for children were homeopathy and herbal medicine (used by 30% and 28% of CM users, respectively). 88% of CM was bought over the counter and 53% of CM use was not reported to their doctor. Parents also used traditional complementary remedies for their children. Conclusions: These results suggest that CM use in children is higher than previously estimated in the UK. This indicates the need for greater professional awareness of CM as part of clinical care. There is a need to acknowledge the beliefs that inform parents’ decision-making process. ?? 2007 Elsevier Ltd. All rights reserved.